Cover Image. Issue 7 (7th July 2017) - Just, J.; Bourgoin‐Heck, M.; Amat, F.
Abstract : The cover image, by J. Just et al., is based on the Original Article Clinical phenotypes in asthma during childhood, DOI10.1111/cea.12939